Clinical guideline utilization in Uganda: A scoping review and comparison - Bola, Rajan; Kihumuro, Raymond Bernard; Ngonzi, Joseph; Lett, Ronald (Tropical Doctor, 2022)
Countries such as Uganda often depend on clinical practice guidelines from developed countries, non-profit charities, and international organizations. The sources and organizations that provide most of the guidelines used in Uganda are not well documented. The primary objective of this article was to determine whether a scoping review of scientific, peer-reviewed literature could identify the clinical guidelines actually used in Uganda. A secondary objective was to examine which organizations provided the majority of guidelines used. We therefore searched for consensus documents, guidelines, and meta-analyses published for use in African countries indexed in PubMed, OVID Medline, and Embase, and then surveyed guidelines currently in use in Ugandan medical practice. We thus compared these two sets of guidelines, as well as their breadth, geography, and sources, to make recommendations for similar low-income countries
Keywords: Clinical practice guidelines; Scoping review; Uganda